Influence of Grazing Intensity on Seed Bank of a Sandy Grassland in Horqin Steppe of China - Zhao, Wenzhi; Liu, Zhimin; Chang, Xueli (Annals of Arid Zone, 2016)
It is well known that grazing influences the quantity and quality of grassland seed banks, and tbat the magnitude of influence depends on the grazing intensity and the bioclimate zone in which the grassland is located. However, very little.is known about seed bank dynamics under different grazing intensities in a sandy grassland of Horqin Steppe. In this study four grazing intensity treatments, i.eoOcontrol (ungrazed, CK), light grazing (2 sheep unit ha,j, L), moderate grazing (4 sheep unit ha’l, M), and heavy grazing (6 sheep unit ha,j, H), were imposed on a sandy rang site. The results showed thai: (i) with the increase of grazing intensity, the number of plant species in the seed hank decreased, but the percentage of annual species increased; (ii) the number of seed bank under both light grazing and moderate grazing tended to increase, but under heavy grazing it tended to decrease; (iii) annual species dominated the seed bank, and with increased grazing intensity, the percentage of the number of seeds of annual species decreased, but that of leguminous plants increased; (iv) under the ungrazed and light grazing conditions the seed density in soil showed a significant correlation with the corresponding plant frequency in the vegetation, whereas under moderate and heavy grazing cO,nditions such correlation was poor